Consumer Motivation On Internet Shopping An Exploratory Study on Consumer Motivation of Online Shopping in Thailand - Ghogar, Vandhana (2010)
The growth of B2C shopping has soared massively over the last few years in Thailand. Although B2C has created an immense amount of new opportunities for Thai companies and businesses, questions still arise about why consumers are motivated to use the Internet as a medium to shop over conventional shopping. Due to the rapid increase in online stores, competition has also risen remarkably. Therefore it is imperative for all online businesses in Thailand to have an understanding of consumer motivation in order to survive in this competitive era. The purpose of this study is to investigate consumer motivations of online shopping in Thailand both in goal-orientated and experiential perspectives. Therefore, this paper proposes a conceptual framework to increase web-developers and online business companies understanding on consumer motivation of online shopping in Thailand. The conceptual framework integrates both goal-orientated and experiential motives and also contains exogenous factors. The goal-orientated motivations in the framework comprises of availability of information, selection, convenience and control of sociality. On the other hand, the experiential motivations include factors such as ambiance, auctions, bargains, adventure and various other factors. Moreover, this study uses a qualitative approach by conducting semi-structured indepth interviews to gather rich insightful data of Thai online consumers. Overall, twenty in-depth interviews were taken by means of the snowballing sampling technique. The study found that Thai consumers are more goal-orientated than experiential especially male consumers. Furthermore, the study found that the most popular utilitarian motivational factors were convenience, selection and availability of information. As for experiential motivations among the Thai respondents, auctions and bargains were yet the most popular between both male and female interviewees. Finally, the study found that exogenous factors such as gender and marital status have an impact towards consumer motivation of online shopping.